Principles of marketing - Kotler, Philip; Armstrong, Gary (New Delhi : Prentice-Hall of India, 2006)
Business
Keywords: Principles of marketing; Marketing process; Consumers; Pricing strategies; Advertising; Sales promotion; Public relation